Eliminating Postoperative Infections on a Budget: Collaborative Quality Improvement for Congenital Heart Surgery in Low- and Middle-Income Countries - Gaies M. (Lippincott Williams and Wilkins, 2018)
10.1161/CIRCOUTCOMES.117.003708